Optimizing Bowel Preparation: An Interprofessional Nursing, Radiology, and Health Assistant Approach to Patient Safety and Diagnostic Accuracy - Alaithan, Wejdan Ibrahim; Ali Hussain Mohammed Salwi; Nasser Hussain Mohammed Tawhari; Mousa Ahmed Ibrahim Bakri; Abdulrhman Mohammed Otayf; Marzog Awwad Alotaibi; Sattam Mansour Abulkhair; Radiyh Abdullah Almarzooq; Norah Yaseen Hassn Alameer; Abdullah Mosawed Hamad Darraj; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Colonoscopy is the gold standard for detecting colorectal pathology, but its diagnostic accuracy depends on adequate bowel preparation. Poor preparation compromises mucosal visualization, increases procedural risk, and leads to missed lesions and repeat procedures. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review bowel preparation strategies, contraindications, and interprofessional roles in optimizing patient safety and diagnostic outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature-based analysis was conducted, synthesizing evidence on preparation regimens, physiologic considerations, contraindications, and team-based interventions. The review emphasizes pharmacologic classifications, dosing strategies, and quality assessment tools such as the Boston Bowel Preparation Scale (BBPS). <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Isosmotic polyethylene glycol (PEG)-based regimens remain the safest and most effective, particularly in patients with comorbidities. Low-volume PEG with ascorbic acid improves tolerability but is contraindicated in G6PD deficiency. Hyposmotic PEG-3350 regimens may cause electrolyte disturbances, while hyperosmotic agents like magnesium citrate and sodium sulfate require caution in renal impairment. Sodium phosphate is largely avoided due to nephropathy risk. Split-dose administration consistently improves cleansing quality and adenoma detection rates. Interprofessional collaboration—physicians, nurses, and pharmacists—enhances adherence and safety, while patient education significantly improves outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective bowel preparation is a multidisciplinary process integrating regimen selection, patient-centered education, and objective quality assessment. Individualized planning and team-based interventions reduce incomplete colonoscopies, improve lesion detection, and enhance patient safety.